A comparative study of pharmacokinetics of coated tablets of mycophenolic acid - A. L. Khokhlov; I. I. Yaichkov; A. M. Shitova; L. N. Shitov; Yu. A. Dzhurko; A. E. Miroshnikov (Фармакокинетика и Фармакодинамика)
In a single-dose, two-treatment, two-period, two-sequence crossover study with a 14-days washout period was carried out the bioequivalence study of two tablet coated formulation of mycophenolic acid that given to 48 volunteers in equal doses (dosage 360 mg). There were calculated the followed parameters: AUC0-t, Cmax, Tmax, Cmax/AUC. 90% confidence interval for ratio of geometric mean AUC0-t values was 98,97% - 111,49% and one for ratio of geometric mean Cmax was 121,27% - 153,94%. The upper limit of the confidence interval of Cmax valuesa goes beyond the permissible range according to the protocol study (75-133%). It is not possible to state bioequivalence of drugs. Possible causes of discrepancies of pharmacokinetic parameters were analyzed.